UNA ESCULTURA DE SAN SEBASTIÁN DEL SIGLO XVI EN CEHEGÍN (MURCIA) - de la Ossa Giménez, Elena (Imafronte, 1993)
In past times, people's devotion to Saints who were thought about as protectors against common sicknesses and epidemics as the bubonic plague and the cholera- led to the realization of works like the Saint Sebastian of Cehegín, a 16th, century anonimous sculpture which is a transitional work between the gothic tradition coming from the Middle Age and the new Renaissance forms. Since the Saint's hermitage was under the patronage of the City Council, the Council minutes contain a great number of references on election of persons in charge, rogations, processions and feasts devoted to the Saint.